The Impact of Free GP Care on GP Utilisation in Ireland - Gorecki, Paul K (The Economic and Social Review, 2018)
The successful implementation of the ongoing roll-out of free GP care for all private patients in Ireland, begun in 2015, requires an estimate of its impact on GP utilisation. However, estimates of this impact vary widely. For example, a recent study based on administrative records of six GP practices, predicts an extra 4.4 million GP visits. This paper argues that little reliance should be placed on this estimate due to methodological and sample selection issues, as well as the use of demonstrably inappropriate assumptions. Instead, more reliance should be placed on estimates derived from retrospective self-reporting surveys (e.g. Growing Up in Ireland, the Irish Longitudinal Study on Ageing) which suggest that extending free GP care to all private patients is likely to result in an increase of around 2.5 million GP visits. The increase in demand for GP services occasioned by free GP care feeds into the wider debate about the enhanced role of primary care in Ireland and the corresponding increase in funding.